The journey of listening to someone: therapists’ meaning-making of the impact of working with sexual abuse survivor groups - Toombes, Alexandra E. (2009)
Introduction The topic of study is concerned with the impact that working with sexual abuse survivor groups has on therapists. The existing literature primarily utilises quantitative methodologies and is, on the whole, concerned with the negative impact of trauma work. Previous studies have suggested that qualitative research exploring the experiences of therapists working in this field would provide a richer understanding of the potential impacts. The methodological limitations and shortcomings of the existing research base are addressed, specifically the lack of research on group therapists.